Stigmatisation of survivors of political persecution in the GDR: attitudes of healthcare professionals - Schott, Tobias; Blume, Marie; Weiß, Anne; Sander, Christian; Schomerus, Georg (Frontiers in Psychiatry, 2025)
IntroductionPeople with mental disorders face various barriers on the road to treatment. People who have experienced injustice of the state apparatus of the German Democratic Republic (GDR) in the form of various reprisals are a group that has received insufficient attention in research. Some of them still show long-term psychological and physical consequences that occur more frequently than in the general population, resulting in an increased need for treatment. There are currently no studies on how those affected are perceived by practitioners due to their history and whether they are exposed to stigmatizing attitudes.MethodA vignette-based survey was carried out to identify possible stigmatising attitudes. An independent opinion and survey institute conducted the study in three phases in December 2022, April 2023 and May to August 2024 using an online survey. A total of N=1357 practitioners from the German healthcare system were presented one of four case vignettes. The two vignettes described a person with mental health difficulties who had either experienced an unremarkable socialization in the GDR (A) or had suffered injustice in the GDR (B). In addition to socio-demographic variables, stereotypes, emotional reactions and desire for social distance towards the person described were recorded.ResultsAge and sex as well as subjective knowledge about the GDR, the occupational group and the working environment influence the intensity of emotional reactions as well as the desire for social distance and the extent of negative stereotypical attitudes. The presentation of a case vignette that deals with an experience of SED injustice favours a decrease in positive and an increase in negative stereotypes. The explanatory power of the regression models is predominantly in the medium range (from 3.7 till 32.3%).ConclusionsEven more than three decades after the reunification of Germany, people with mental health problems and an experience of SED injustice in the GDR still experience stigmatizing attitudes on the part of those treating them. Stigmatizing attitudes can affect treatment and care.